Optimal Placement of Fuzzy based UPQC Topologies with Distributed Generation for Power Quality Enhancement in IEEE 14 Bus System - R. Sukhesh, H.; Vadivu U., Senthil; Karthikey, Prabhakar; ., . (International Journal of Engineering and Technology, 2018)
An Unified Power Quality Conditioner (UPQC), is a combination of shunt and series Active Power Filter (APF), has become a standard accepted solution in the area of current and voltage harmonics mitigation of a power system network. This paper furnishes a comparative analysis of the power quality enhancement and optimization in positioning for three different VSI based UPQC system configurations namely: 3P3W UPQC topology, 3P4W UPQC based on 2C shunt inverter topology and 3P4W UPQC based on 4L shunt inverter topology, all supported with the Fuzzy Logic Controller (FLC), placed at different locations in a standard IEEE 14 bus system. Simulation results using MATLAB/SIMULINK provides the optimal position of UPQC for mitigating the harmonic issues in the standard IEEE 14 bus system.Â Â